1982
DOI: 10.1111/j.1471-0307.1982.tb02259.x
|View full text |Cite
|
Sign up to set email alerts
|

Structures of the triglycerides of cows' milk, fortified milks (including. infant formulae), and human milk

Abstract: The positional distributions of fatty acids in triglycerides from cows' milk, cows' milk enriched in linoleic acid by dietary means, and two commercial infant formulae fortified with vegetable fats have been determined for comparison with human milk. The results are discussed in terms of the digestibility of the fats and of the requirements of the human infant for linoleic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
1
2

Year Published

1988
1988
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 12 publications
7
44
1
2
Order By: Relevance
“…The relative ratio of β-PPC and β-PCP in human milk was different from that of ruminants, and more than half of the medium-chain fatty acids were located at the β position, namely 67.4 was β-PCP Table 3 . In fact, it had been previously reported that the medium-chain fatty acid was distributed mainly at the sn-3 position in human milk 10,25 ; however, this was not consistent with our results. It is known that milk TAG is synthesized in mammary tissue by the glycerol-3-phosphate pathway 26,27 .…”
Section: Resultscontrasting
confidence: 99%
“…The relative ratio of β-PPC and β-PCP in human milk was different from that of ruminants, and more than half of the medium-chain fatty acids were located at the β position, namely 67.4 was β-PCP Table 3 . In fact, it had been previously reported that the medium-chain fatty acid was distributed mainly at the sn-3 position in human milk 10,25 ; however, this was not consistent with our results. It is known that milk TAG is synthesized in mammary tissue by the glycerol-3-phosphate pathway 26,27 .…”
Section: Resultscontrasting
confidence: 99%
“…The analysis was performed on short-chain and long-chain TAG of both fats after we had fractionated TAG by thinlayer chromatography (20 × 20 plates, 0.25 µm of silica gel thickness, SDS, Peypin, France), as required for dairy fat [10]. For both the short-chain and the long-chain TAG, representative acylglycerols (diacyl-1,3-sn-glycerol, 1,2(2,3)-diacyl-rac-glycerol, 2-monoacyl-sn-glycerol, 1(3)-monoacyl-rac-glycerol) were generated from the original TAG by partial Grignard degradation.…”
Section: Methodsmentioning
confidence: 99%
“…15,28,29 A gordura apresenta-se na forma de glóbulos de cerca de 4 µm de diâmetro em emulsão de óleo em água, estabilizada por uma membrana contendo fosfolipídios e proteínas. 30,31 Valores médios para os teores de gordura do leite humano, incluindo os ácidos graxos, estão disponíveis nos dados de nutrição do United States Departament of Agriculture. 32 Agostoni et al 33 estudaram o conteúdo de gordura total e os ácidos graxos no colostro e ao longo de 12 meses de lactação, o total de ácidos graxos poliinsaturados (PUFAs), as concentrações de ácido araquidônico (AA -20:4 n-6) e de ácido docosaexaenóico (DHA -22:6 n-3), que permaneceram estáveis do colostro até os 12 meses de lactação.…”
Section: Gordura Do Leite Humanounclassified